Freeze-induced crystallization: An overlooked pathway for mineral genesis in natural waters - Younghoon Won; Sungsik Lee; Seungyeol Lee; SoHyun Park; Jun Lim; Wonyong Choi; Giehyeon Lee (Proceedings of the National Academy of Sciences, 2025)
Natural ice plays salient roles in making the Earth habitable and sustainable. Previously overlooked, its role in chemical processes is now of emerging interest, particularly due to the freeze concentration effect, which can substantially promote chemical reactions during ice formation. We demonstrate here that ice formation can serve as a dynamic and unique pathway for mineral genesis. Freezing solutions containing dissolved manganese and carbonates produced rhodochrosite (Mn II CO 3 ) even under slightly undersaturated conditions. At room temperature, by contrast, this occurred when the solution saturation level was increased by ca. 30,000 times. The cryogenic rhodochrosite formed spherical aggregates of nano-polycrystallites, distinctly different from the cubic monocrystalline particles observed at room temperature. The distinct feature likely resulted from the combined effects of the intensified supersaturation induced by the freeze concentration effect and the low temperatures within liquid-like layers, conditions that make liquid-like layers an exceptional environment for mineral genesis, unlike typical natural water systems. The cryogenic rhodochrosite formation was successfully demonstrated using in situ, real-time X-ray absorption spectroscopy (XAS), enabling direct observation of freeze-induced solid formation. Our findings reveal that freeze-induced crystallization may be an active mineralization pathway, potentially influencing elemental cycles within the cryosphere and contributing to minerals with distinguishing properties and reactivities in the environment.